Early-Life Nutritional Factors and Mucosal Immunity in the Development of Autoimmune Diabetes - Xiao, Ling; van’t Land, Belinda; van de Worp, Wouter R. P. H.; Stahl, Bernd; Folkerts, Gert; Garssen, Johan (Frontiers in Immunology, 2017)
Type 1 diabetes (T1D) is an immune-mediated disease with a strong genetic basis but might be influenced by non-genetic factors such as microbiome development that “programs” the immune system during early life as well. Factors influencing pathogenesis, including a leaky intestinal mucosal barrier, an aberrant gut microbiota composition, and an altered immune responsiveness, offer potential targets for prevention and/or treatment of T1D through nutritional or pharmacologic means. In this review, nutritional approaches during early life in order to protect against T1D development have been discussed. The critical role of tolerogenic dendritic cells (tDCs) in the central and peripheral tolerance has been emphasized. In addition, since the gut microbiota affects the development of T1D through short chain fatty acids (SCFA) -dependent mechanisms, we hypothesize that nutritional intervention boosting SCFA production may be used suggested as a novel prevention strategy. Current retrospective evidence has suggested that exclusive and prolonged breastfeeding might play a protective role against the development of T1D. The beneficial properties of human milk are possibly attributed to its bioactive components such as unique immune modulatory components human milk oligosaccharides (HMOs) and metabolites derived thereof including / for example SCFAs. These components might play a key role in healthy immune development and creating a fit and resilient immune system in early and later life.